Tocilizumab in rheumatoid arthritis: efficacy, safety and its place in therapy - Kaneko, Atsushi (SAGE Publications, 2013)
Tocilizumab is a humanized antihuman interleukin-6 (IL-6) receptor monoclonal antibody. It was developed in Japan as the first biological disease-modifying antirheumatic drug targeting IL-6 receptors. Many large-scale global studies have demonstrated its efficacy and safety, and in April 2008 it was approved in Japan for use in the treatment of rheumatoid arthritis, sooner than in other countries. In this paper, I review the efficacy and safety of tocilizumab in the light of front-line clinical data and data from large-scale studies, and I consider the place of tocilizumab treatment in real clinical practice.